Reuse of Industrial By-products in Construction using Geopolymerization - Manukhina Lyubov; Sreejyothsna Ankam; Logabiraman Govardhan; Dhawan Aashim; Kumar Rakesh; Anand Sami; Sarpal Sumeet Singh; Sharma Prashant; Hassan Muntather Muhsin (E3S Web of Conferences)
This study explores the reuse of industrial by-products in construction through geopolymerization, positioning it as a sustainable alternative to conventional construction materials. In light of the growing demand for environmentally friendly building practices, this research aims to evaluate geopolymer concrete made with industrial by-products as a viable substitute for traditional concrete. The introduction highlights the importance of sustainable construction and the potential of geopolymer technology in reducing environmental impacts. A comprehensive review of the composition, properties, and previous studies on geopolymer concrete using industrial waste materials is provided. The research methodology outlines the objectives, materials used, experimental framework, and testing protocols. Results on compressive strength, flexural strength, and durability of the geopolymer concrete samples are discussed in detail in the results and analysis section. The discussion interprets the findings, focusing on the enhanced strength and durability achieved through the incorporation of industrial by-products. The study concludes with a summary of key outcomes, implications for the construction industry, and recommendations for future applications and research on geopolymer concrete using industrial waste.